Dual antibacterial mechanism of [K4K15]CZS-1 against Salmonella Typhimurium: a membrane active and intracellular-targeting antimicrobial peptide - Bermúdez-Puga, Sebastián; Dias, Meriellen; Freire de Oliveira, Taciana; Mendonça, Carlos Miguel Nóbrega; Yokomizo de Almeida, Sonia Regina; Rozas, Enrique Eduardo; do Nascimento, Claudio Augusto Oller; Mendes, Maria Anita; Oliveira De Souza de Azevedo, Pamela; Almeida, José R.; Proaño-Bolaños, Carolina; Oliveira, Ricardo Pinheiro de Souza (Frontiers in Microbiology, 2023)
Salmonella genus is a leading cause of food-borne infections with strong public health impact and economic ramifications. The development of antimicrobial resistance added complexity to this scenario and turned the antibiotic drug discovery into a highly important challenge. The screening of peptides has served as a successful discovery platform to design new antibiotic candidates. Motivated by this, the antimicrobial and cytotoxic properties of three cruzioseptins against Salmonella Typhimurium and RAW 264.7 murine macrophage cells, respectively, were investigated. [K4K15]CZS-1 was the most potent antimicrobial peptide identified in the screening step with a minimum inhibitory concentration (MIC) of 16 μg/mL (7.26 μM) and moderate cytotoxicity. From a structural point of view, in vitro and in silico techniques evidenced that [K4K15]CZS-1 is a α-helical cationic antimicrobial peptide. In order to capture mechanistic details and fully decipher their antibacterial action, we adopted a multidimensional approach, including spectroscopy, electron microscopy and omics analysis. In general lines,[K4K15]CZS-1 caused membrane damage, intracellular alterations in Salmonella and modulated metabolic pathways, such as the tricarboxylic acid (TCA) cycle, fatty acid biosynthesis, and lipid metabolism. Overall, these findings provide deeper insights into the antibacterial properties and multidimensional mode of action of [K4K15]CZS-1 against Salmonella Typhimurium. In summary, this study represents a first step toward the screening of membrane-acting and intracellular-targeting peptides as potential biopreservatives to prevent foodborne outbreaks caused by Salmonella.